On optimization of the pid governor for diesel engine - Malkhede, D. N.; Dhariwal, H. C.; Joshi, M. C. (Mathematical Modelling and Analysis, 2002)
In a diesel engine, governor is indispensable for ensuring that the engine maintains a certain speed under various load conditions, that the engine speed does not exceed a certain speed as a protection against self‐destruction or stall. Also, speed fluctuations resulting from poor governing, lead to vibrations, noise, wear and tear and increased level of soot. Therefore it is desirable to have minimum speed fluctuations under all engine‐operating conditions. Inspite of many limitations, most of the existing engines still use simple mechanical governor providing proportional control only. Electronic governors can provide a more flexible P (proportional), I (integral), and D (derivative) control under all speeds and loads. So far no work is reported on optimizing the controller parameters using the analytical approach. In the present work turbo charged diesel engine is analytically modeled based on Krutov's approach for the control analysis. Attempts have been made to optimize controller parameters. The criterion for minimizing the engine speed fluctuations is met by minimizing the Integral Squared Error in engine speed. The parameters obtained have been used to study the engine speed response. The results have shown remarkable improvement in the engine speed fluctuations.Dyzelinio variklio PID reguliatoriaus optimizavimasSantrauka. Dyzeliniame variklyje reguliatorius turi palaikyti nustatytą apsisukimų skaičių prie įvairių apkrovimo sąlygų, taip, kad variklio apsisukimų skaičius neviršytų tam tikros ribos, prie kurios variklis genda, arba užgęsta. Apsisukimu svyravimai sukelia vibraciją, triukšmą, nusidėvėjimą, įplyšimus ir padidėja suodžių kiekis. Todėl pageidautina esant įvairioms valdymo sąlygoms turėti minimalius apsisukimų skaičiaus svyravimus. Daugelis eksploatuojamų variklių, nepaisant nurodytų trūkumų, naudoja paprastą mechaninį valdymą, atsižvelgiantį tik į proporcingus pokyčius. Šiame darbe turbokompresoriniam dyzeliniam varikliui, panaudojus Krutovo analizės metodą sudarytas modelis, kuriame optimizuojami valdymo parametrai. Variklio apsisukimų skaičiaus svyravumų minimizavimui naudojama jų integralinės kvadratinės paklaidos analizė. Gauti parametrai panaudoti variklio reakcijai į apsisukimų greitį nagrinėti. Rezultatai rodo žymų variklio apsisukimų skaičiaus svyravimų reguliavimo pagerinimą. First Published Online: 14 Oct 2010